Precious metal-doped NiV layered double hydroxide catalyst as well as preparation method and application thereof

By doping precious metals into NiV layered double hydroxide catalysts, the precious metal doped NiV layered double hydroxide catalysts are solved, and the problem of high cost and low efficiency of electrolyzed seawater hydrogen production catalysts is achieved, and efficient and stable electrolysis is achieved Hydrogen production performance in seawater.

CN119392297APending Publication Date: 2025-02-07SHENZHEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411556389.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing electrolytic seawater hydrogen production catalysts are costly and have low efficiency, and rely on a large number of precious metals, which limits large-scale commercial production.

Method used

Using precious metal doped NiV layered double hydroxide catalyst, the precious metals platinum, osmium, ruthenium, iridium, rhodium or palladium are anchored on the NiV layered double hydroxide through a simple anchoring method, and are used to electrolyze seawater to make hydrogen . The catalyst achieves ultra-long stability under alkaline seawater conditions and is able to operate on the HER side and OER side for more than 2000 hours.

Benefits of technology

It realizes the efficient performance of electrolyzing seawater to produce hydrogen under industrial current density, with a current density of up to 1000mAcm-2, and has high stability and low cost, which can effectively reduce the amount of precious metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392297A_ABST
    Figure CN119392297A_ABST
Patent Text Reader

Abstract

The invention discloses a noble metal-doped NiV layered double hydroxide catalyst as well as a preparation method and application thereof, relates to a noble metal-doped nickel-based electrocatalyst for hydrogen evolution reaction and oxygen evolution reaction as well as a preparation method and application thereof, and aims to solve the technical problems of high cost and low efficiency of an existing seawater-electrolysis hydrogen production catalyst. According to the catalyst, foamed nickel serves as a substrate, micron-sized NiV layered double hydroxide grows on the surface of the foamed nickel in situ, and the NiV layered double hydroxide contains precious metal platinum, osmium, ruthenium, iridium, rhodium or palladium. The preparation method comprises the following steps: putting foamed nickel into a mixed solution of nickel nitrate, vanadium chloride and precious metal salt for hydrothermal reaction, cleaning, and drying. In alkaline seawater, under the current density of 10 mA cm <-2 >, the overpotential of the catalyst doped with ruthenium on the HER side is only 48 mV, and the stability exceeds 2400 h; the overpotential of the catalyst doped with iridium on the OER side is only 202 mV, the stability exceeds 2750 h, and the catalyst can be used in the field of hydrogen production through seawater electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nickel-based electrocatalyst doped with noble metals for hydrogen evolution reaction and oxygen evolution reaction, and belongs to the field of new energy material technology and hydrogen production by electrolysis of water. Background Art

[0002] As a clean and safe energy carrier, hydrogen energy has an energy density of up to 120 kJ / g and is an ideal bridge for the transition from fossil energy to clean energy. In the process of hydrogen production, water electrolysis (especially seawater electrolysis) is considered to be an effective way to obtain hydrogen energy, especially using cheap renewable energy. Mature commercial systems for hydrogen production by water electrolysis include alkaline electrolyzers (ALK), proton exchange membrane electrolyzers (PEM), high-temperature solid oxide electrolyzers (SOEC) and anion membrane electrolyzers (AEM). However, more than 50% of the current cost of these electrolyzers comes from the preparation of bipolar plates (catalyst layers), especially the cathode proton exchange membrane of PEM needs to be hot-pressed or transferred with a large amount of expensive precious metal slurry, which significantly increases the overall cost and limits large-scale commercial promotion. In addition, water electrolysis for hydrogen production also faces the problem of raw material use. Both alkaline electrolyzers and proton exchange membrane electrolyzers require high-purity water as raw materials. However, the world's fresh water resources are limited. If hydrogen production relies on high-purity water in the future, the problem of fresh water consumption will not be ignored. In contrast, seawater accounts for 96.5% of the Earth's water reserves and is an almost unlimited resource. Despite the obvious advantages of seawater electrolysis, there are still many challenges, including the toxic effects of impurity ions, competition from chloride ion oxidation reactions, and corrosion caused by local pH reduction in seawater. Therefore, the development of highly active electrolytic catalysts that can be used in seawater for a long time is the key to promoting hydrogen production from seawater. At present, the cathode (HER side) of commercial electrolyzers generally uses a large amount of precious metal-based catalysts, and the anode (OER side) also relies on a large amount of precious metal-based catalysts. Due to their limited resources and expensive prices, this further pushes up the cost of hydrogen production. Therefore, in the face of the rapid development of the hydrogen energy industry, it is urgent to find more economical and less precious metal-introduced effective catalyst materials and innovative technologies for electrolysis of seawater to produce hydrogen in order to achieve large-scale commercial production. Summary of the invention

[0003] The present invention aims to solve the technical problems of high cost and low efficiency of the existing electrolysis of seawater hydrogen production catalyst, and provide a noble metal doped NiV layered double hydroxide catalyst and its preparation method and application. The present invention uses simple doping modification to prepare a noble metal doped NiV layered double hydroxide catalyst, which can be used for anode (oxygen evolution) and cathode (hydrogen evolution) catalysis by doping different noble metals, and the catalyst achieves ultra-long stability of more than 2000 hours on the HER side and more than 2000 hours on the OER side under alkaline seawater conditions. The catalyst uses a simple anchoring method to anchor noble metal platinum, osmium, ruthenium, iridium, rhodium or palladium on the NiV layered double hydroxide, and is used to electrolyze seawater to produce hydrogen at industrial current density.

[0004] The noble metal doped NiV layered double hydroxide catalyst of the present invention is based on nickel foam, and in situ grows micron-sized NiV layered double hydroxide on the surface of nickel foam, and the NiV layered double hydroxide contains noble metal; wherein the noble metal is platinum, osmium, ruthenium, iridium, rhodium or palladium.

[0005] The method for preparing the noble metal-doped NiV layered double hydroxide catalyst of the present invention is carried out according to the following steps:

[0006] 1. Placing the nickel foam in dilute acid, organic solvent and anhydrous ethanol in turn for ultrasonic treatment, and then washing with anhydrous ethanol to obtain clean nickel foam;

[0007] 2. Using Ni(NO 3 ) 2 6H 2 O、VCl 3 and precious metal salts to prepare a metal salt mixed solution; then the metal salt mixed solution is transferred to a hydrothermal synthesis reactor, the clean nickel foam is immersed in the metal salt mixed solution, the reactor is sealed and placed in a furnace at a temperature of 120-200° C. for hydrothermal reaction for 10-15 hours, after the reaction is completed, the nickel foam is taken out and cleaned to obtain a nickel foam with micron-sized layered double hydroxide in situ grown on the surface.

[0008] 3. Drying the nickel foam with micron-sized layered double hydroxide in situ grown on the surface to obtain a noble metal-doped NiV layered double hydroxide catalyst.

[0009] Preferably, the dilute acid in step 1 is hydrochloric acid with a concentration of 3 to 12 mol / L.

[0010] Preferably, the organic solvent in step 1 is one or more of acetone, isopropyl ketone and ethylene glycol.

[0011] Preferably, the noble metal salt in step 1 is a chloride of platinum, osmium, ruthenium, iridium, rhodium or palladium.

[0012] Preferably, the metal salt mixed solution in step 2 contains Ni(NO 3 ) 2 6H 2 O、VCl 3 The molar ratio of the precious metal salt is 1:(0.7-8):(0.5-2);

[0013] Preferably, the metal salt mixed solution in step 2 contains Ni(NO 3 ) 2 6H 2 The concentration of O is 0.01 to 1 mmol / mL.

[0014] Preferably, the drying in step 3 is natural drying or vacuum drying at a temperature of 50 to 80° C. for 1 to 5 hours.

[0015] The application of the above-mentioned noble metal doped NiV layered double hydroxide catalyst is to use the noble metal doped NiV layered double hydroxide catalyst for electrolysis of seawater to produce hydrogen. At present, the current density for hydrogen production in industrial electrolysis of seawater is required to be ≥400mAcm -2 The current density of the noble metal-doped NiV layered double hydroxide catalyst in the electrolysis of seawater to produce hydrogen can reach 1000 mA cm -2 , can work under high current to improve hydrogen production efficiency.

[0016] The microscopic morphology of the noble metal-doped NiV layered double hydroxide catalyst of the present invention is a micron-sized lamellar double hydroxide grown in situ, and the layered double hydroxide contains noble metals, which provides a large number of active sites for the catalyst, and is a noble metal-doped nickel-based electrocatalyst. The noble metal and nickel-based multiple catalytic active sites are constructed step by step on the foamed nickel matrix, and the preparation method is simple and low in cost.

[0017] The preparation method of the present invention is to place the noble metal-doped NiV layered double hydroxide catalyst in 1M KOH seawater at 10 mA cm -2 At a current density of 1.5 MW, the overpotential of the catalyst doped with precious metal Ru on the HER side is only 48 mV, and the overpotential of the catalyst doped with precious metal Ir on the OER side is only 202 mV. In alkaline seawater, the HER stability of the catalyst doped with precious metal Ru exceeds 2400 h (about 100 days), and the OER stability of the catalyst doped with precious metal Ir exceeds 2750 h (about 114 days), showing the characteristics of high stability and high activity.

[0018] The catalyst of the noble metal-doped NiV layered double hydroxide of the present invention is an excellent catalyst, has excellent electrochemical catalytic performance in electrolyzing seawater, and can be used in the field of high-current electrolysis of seawater for hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a SEM image of the IrNiVLDH prepared in Example 1 at a scale of 50 μm;

[0020] Figure 2 This is a SEM image of the IrNiVLDH prepared in Example 1 at a scale of 20 μm;

[0021] Figure 3 This is a SEM image of the IrNiVLDH prepared in Example 1 at a scale of 5 μm;

[0022] Figure 4 The XRD characterization results of IrNiVLDH prepared in Example 1 are compared with the standard card;

[0023] Figure 5 TEM image of NiVLDH prepared in Example 3 and energy spectrum of the elements contained therein;

[0024] Figure 6 TEM image of RuNiVLDH prepared in Example 2 and energy spectrum of the elements contained therein;

[0025] Figure 7 TEM image of IrNiVLDH prepared in Example 1 and energy spectrum of the elements contained therein;

[0026] Figure 8 The hydrogen evolution polarization curves of IrNiVLDH prepared in Example 1 and the comparative catalyst in seawater;

[0027] Fig. 9 The RuNiVLDH prepared in Example 2 was -500 mA cm -2 A graph showing the change of potential over time under constant current;

[0028] Fig.10 The oxygen evolution polarization curves of IrNiVLDH prepared in Example 1 and the comparative catalyst in seawater;

[0029] Fig.11 The IrNiVLDH prepared in Example 1 was -2 A graph showing the change of potential over time under constant current;

[0030] Fig.12 This is the polarization curve of the simulated electrolytic cell. DETAILED DESCRIPTION

[0031] The beneficial effects of the present invention are verified by the following examples.

[0032] Example 1: The preparation method of the noble metal Ir-doped NiV layered double hydroxide catalyst of this example is carried out according to the following steps:

[0033] 1. Cut the nickel foam into sizes of 2cm×3cm, 3cm×4cm, and 4cm×4cm, and then place them in 6M hydrochloric acid, acetone, and anhydrous ethanol and clean them with ultrasound for 10 minutes each. The hydrochloric acid is used to wash away the oxide layer on the surface of the nickel foam, the acetone is used to degrease the nickel foam, and the anhydrous ethanol is used to wash away the residual acetone and hydrochloric acid on the nickel foam. Then wash it with ethanol and deionized water, and take it out after cleaning to obtain a clean nickel foam;

[0034] 2. 0.48mmol Ni(NO 3 ) 2 6H 2 O, 0.36mmol VCl 3 and 0.24 mmol IrCl 3 ·xH 2 O is dissolved in 30 mL of deionized water, and stirred on a magnetic stirrer for 30 min to completely dissolve it, to obtain a metal salt mixed solution; the metal salt mixed solution is transferred to a hydrothermal synthesis reactor, and the clean nickel foam is immersed in the metal salt mixed solution. The reactor is sealed and placed in a furnace at a temperature of 120° C. for hydrothermal reaction for 12 h. After the reaction is completed, the nickel foam is taken out and cleaned to obtain a nickel foam with micron-sized lamellar double hydroxide in situ grown on the surface;

[0035] 3. The nickel foam with in-situ grown micron-sized lamellar double hydroxide on the surface was placed in a vacuum drying oven at 80°C and vacuum dried for 1 hour to obtain a noble metal Ir-doped NiV layered double hydroxide catalyst, which was recorded as IrNiVLDH.

[0036] Example 2: This comparative example is to prepare a noble metal Ru-doped NiV layered double hydroxide catalyst. The difference between this comparative example and Example 1 is that 0.24 mmol of IrCl 3 ·xH 2 O was replaced by 0.24 mmol of RuCl 3 ·xH 2 O, and the other steps and parameters are the same as those in Example 1, to obtain a noble metal Ru-doped NiV layered double hydroxide catalyst, denoted as RuNiVLDH.

[0037] Example 3: This comparative example is to prepare a NiV layered double hydroxide catalyst without noble metal doping. The difference between this comparative example and Example 1 is that 0.24 mmol of IrCl in step 2 is omitted. 3 ·xH 2 O, and the other steps and parameters were the same as those in Example 1 to obtain a NiV layered double hydroxide catalyst, denoted as NiVLDH.

[0038] Comparative Example 1: In this comparative example, a comparative Pt / C catalyst was prepared by dropping the mixed slurry onto nickel foam. The specific preparation method is as follows:

[0039] 1. Mix 60 μL nafion, 540 μL deionized water and 400 μL anhydrous ethanol, add 20 mg commercial Pt / C, mix and treat by ultrasound for 30 min to obtain a mixed slurry;

[0040] 2. Take 200 μl of the mixed slurry and drip it on a 1.5×1 cm 2 The Pt / C catalyst was obtained by placing the nickel foam on a clean surface and then placing the nickel foam under a baking lamp and drying it at 80°C for 1 hour to obtain a Pt / C catalyst.

[0041] Comparative Example 2: This comparative example is to prepare comparative ruthenium oxide (RuO 2 ) catalyst, the specific preparation method is as follows:

[0042] 1. Mix 60 μL of Nafion, 540 μL of deionized water and 400 μL of anhydrous ethanol, and then add 20 mg of RuO 2 , and then subjected to ultrasonic treatment for 30 min to obtain a mixed slurry;

[0043] 2. Take 200 μl of the mixed slurry and drip it on a 1.5×1 cm 2 The clean nickel foam was placed under a baking lamp and dried at 80 °C for 8 h to obtain RuO 2 catalyst.

[0044] Figure 1 , Figure 2 and Figure 3 These are SEM photos of IrNiVLDH prepared in Example 1 at different scales. It can be seen from the figures that micron-scale lamellar catalysts are distributed on the nickel foam substrate, and a large number of lamellar crystals can be observed from the large-magnification SEM photos.

[0045] Figure 4 The X-ray diffraction spectrum of IrNiVLDH prepared in Example 1 is compared with the known phase spectrum, and it can be seen that IrNiVLDH is composed of NiVLDH doped with precious metals. 6.56 V 1.44 (OH) 16 (CO 3 ) 0.72 It can also be seen from the phase composition of the material that the NiVLDH prepared in Example 1 is a layered double hydroxide.

[0046] Figure 5The TEM image of IrNiVLDH prepared in Example 1 and the energy spectrum of the elements contained therein clearly show the element distribution of the catalyst. In addition to C, O, Ni and V, IrNiVLDH also contains the precious metal element Ir.

[0047] Figure 6 The TEM image of RuNiVLDH prepared in Example 2 and the energy spectrum diagram containing elements clearly show the element distribution of the catalyst. In addition to C, O, Ni and V, it also contains the precious metal element Ru.

[0048] Figure 7 The TEM image of NiVLDH prepared in Example 3 and the energy spectrum diagram containing elements clearly show the element distribution of the catalyst. NiVLDH contains C, O, Ni and V, but no precious metal elements.

[0049] The ICP test results of IrNiVLDH, RuNiVLDH and NiVLDH prepared in Examples 1, 2 and 3 are shown in Table 1, which clearly shows that compared with Example 3, Example 1 and Example 2 are doped with Ir and Ru, respectively.

[0050] Table 1 ICP test results of IrNiVLDH, RuNiVLDH and NiVLDH prepared in Examples 1, 2 and 3

[0051]

[0052] Figure 8 The hydrogen evolution polarization curves obtained by linear sweep voltammetry LSV test using the noble metal Ir-doped NiV layered double hydroxide IrNiVLDH prepared in Example 1, the RuNiVLDH prepared in Example 2, the NiVLDH prepared in Example 3, and the Pt / C catalyst prepared in Comparative Example 1 as hydrogen evolution catalysts, respectively, are as follows: a three-electrode test system consisting of a working electrode, a counter electrode, and a reference electrode is connected to an electrochemical workstation, and a scan is performed between -0.8V and -3V at a scan rate of 5mV / s to obtain hydrogen evolution polarization curves of each catalyst in alkaline seawater. By comparison, it can be seen that the RuNiVLDH prepared in Example 2 has the best performance as the catalyst, showing 48mV@10mAcm in seawater. -2 It should be emphasized that the noble metal Ru-doped NiV layered double hydroxide catalyst RuNiVLDH prepared in Example 2 exhibits an intrinsic activity comparable to that of commercial Pt / C, and performs much better than commercial Pt / C at high current density. The alkaline seawater used in the test was prepared by adding 1 mol of KOH to a 1 L volumetric flask and then making up the volume with seawater.

[0053] Fig. 9 The noble metal Ru-doped NiV layered double hydroxide catalyst RuNiVLDH prepared in Example 1 was used as a hydrogen evolution catalyst at -500 mA cm -2 The curve of the potential changing with time under constant current, from Fig. 9 It can be seen that the noble metal Ru-doped NiV layered double hydroxide catalyst RuNiVLDH prepared in Example 2 has a high conductivity under alkaline seawater at 500 mA cm -2 The performance of the electrode was almost not significantly degraded after running stably for more than 2400 hours (100 days) under the condition of 1.5 % MgO. The reason is that V was partially dissolved and VO was formed on the electrode surface. 4 3- Layer, VO 4 3- Works synergistically with precious metals to protect electrodes, VO 4 3- The layer can first bind some Ca 2+ ,Mg 2+ , then the noble metal can repel Ca 2+ ,Mg 2+ , to avoid the formation of Ca(OH) 2 , Mg(OH) 2 The formation of an obstacle to the electrode reaction, the combined effect of improving the stability of the electrode and protecting the electrode, indicates that the noble metal Ru-doped NiV layered double hydroxide catalyst RuNiVLDH prepared in Example 1 has excellent stability as a hydrogen evolution catalyst.

[0054] Fig.10 The noble metal Ir-doped NiV layered double hydroxide catalyst IrNiVLDH prepared in Example 1, RuNiVLDH prepared in Example 2, NiVLDH prepared in Example 3, and RuO prepared in Comparative Example 2 were used to prepare the catalyst. 2 The catalysts were used as oxygen evolution catalysts for linear sweep voltammetry (LSV) test to obtain oxygen evolution polarization curves. The specific test method is as follows: a three-electrode test system consisting of a working electrode, a counter electrode and a reference electrode was connected to an electrochemical workstation, and a scan was performed between 0 and 2 V at a scan rate of 5 mV / s to obtain oxygen evolution polarization curves of each catalyst in seawater. By comparison, it can be seen that under alkaline seawater conditions, the performance of the noble metal Ir-doped NiV layered double hydroxide catalyst IrNiVLDH prepared in Example 1 is better than that of the comparative example, showing 202 mV@10 mA cm in seawater. -2 Compared with commercially selected ruthenium oxide catalysts, IrNiVLDH outperforms commercial RuO 2 The intrinsic activity of RuO is much better than that of commercial RuO at high current density. 2 .

[0055] Fig.11The noble metal Ir-doped NiV layered double hydroxide catalyst IrNiVLDH prepared in Example 1 was subjected to the conditions of seawater and 500 mA cm -2 The curve of potential changing with time under constant current, from Fig.11 It can be seen that in alkaline seawater 500mA / cm 2 The performance of the electrode was slightly degraded after stably running for more than 2750 hours under the condition of 1.5 % MgO. The reason is that V was partially dissolved and VO was formed on the electrode surface. 4 3- Layer, VO 4 3- Works synergistically with precious metals to protect electrodes, VO 4 3- The layer can first exclude some Cl - , then the noble metal can combine with Cl - , avoiding the formation of chlorine evolution reaction and damaging the electrode, and working together to improve the stability of the electrode and protect the electrode.

[0056] Fig.12 In order to verify the practicality of the noble metal doped NiV layered double hydroxide catalysts of Examples 1 and 2, a noble metal Ru doped NiV layered double hydroxide catalyst and a noble metal Ir doped NiV layered double hydroxide catalyst of size 2 cm×2 cm were assembled into a simulated electrolyzer as catalysts on the hydrogen evolution side and oxygen evolution side, respectively, to obtain a simulated electrolyzer. The polarization curves in the simulated electrolyzer are shown in FIG. Fig.12 It can be seen that the catalysts of Example 1 and Example 2 prepared on a large scale are assembled in an electrolytic cell and compared with the nickel foam assembled in the electrolytic cell. It is found that the simulated electrolytic cell equipped with Example 1 and Example 2 has better electrocatalytic performance.

[0057] The noble metal-doped NiV layered double hydroxide catalyst of the present invention is a nickel-based electrocatalyst, and its electrocatalytic performance is further improved by doping a small amount of noble metal, which can not only reduce the use of noble metals, but also maintain its high activity, making it the most potential alternative to the noble metals Pt and RuO 2 The catalyst also has high efficiency, long life and can meet the industrial current density of 400mA cm -2 It has the characteristics of use and can be used as a catalyst for both cathode and anode at the same time. It is used in the field of hydrogen production by electrolysis of seawater, which can solve the problems of high catalyst cost and complex process in the current field of hydrogen production by electrolysis of seawater.

Claims

1. A noble metal-doped NiV layered double hydroxide catalyst, characterized in that: The catalyst is based on nickel foam, and micron-sized NiV layered double hydroxide is in-situ grown on the surface of nickel foam, and the NiV layered double hydroxide contains precious metals; wherein the precious metals are platinum, osmium, ruthenium, iridium, rhodium or palladium.

2. A method for preparing the noble metal-doped NiV layered double hydroxide catalyst according to claim 1, characterized in that: The method proceeds as follows:

1. Placing the nickel foam in dilute acid, organic solvent and anhydrous ethanol in turn for ultrasonic treatment, and then washing with anhydrous ethanol to obtain clean nickel foam; 2. Prepare a metal salt mixed solution using Ni(NO3)2·6H2O, VCl3 and precious metal salts; then transfer the metal salt mixed solution to a hydrothermal synthesis reactor, immerse the clean nickel foam in the metal salt mixed solution, seal the reactor and place it in a furnace at a temperature of 120-200°C for hydrothermal reaction for 10-15 hours. After the reaction is completed, take out and clean the nickel foam to obtain a nickel foam with in-situ growth of micron-sized layered double hydroxide on the surface.

3. Drying the nickel foam with micron-sized layered double hydroxide in situ grown on the surface to obtain a noble metal-doped NiV layered double hydroxide catalyst.

3. The method for preparing the noble metal-doped NiV layered double hydroxide catalyst according to claim 2, characterized in that: The dilute acid described in step 1 is hydrochloric acid with a concentration of 3 to 12 mol / L.

4. The method for preparing a noble metal-doped NiV layered double hydroxide catalyst according to claim 2 or 3, characterized in that: The organic solvent described in step 1 is one or more of acetone, isopropyl ketone and ethylene glycol.

5. The method for preparing a noble metal-doped NiV layered double hydroxide catalyst according to claim 2 or 3, characterized in that: The noble metal salt described in step 1 is a chloride of platinum, osmium, ruthenium, iridium, rhodium or palladium.

6. The method for preparing a noble metal-doped NiV layered double hydroxide catalyst according to claim 2 or 3, characterized in that: The molar ratio of Ni(NO3)2·6H2O, VCl3 and precious metal salt in the metal salt mixed solution described in step 2 is 1:(0.7-8):(0.5-2).

7. The method for preparing a noble metal-doped NiV layered double hydroxide catalyst according to claim 2 or 3, characterized in that: The concentration of Ni(NO3)2·6H2O in the metal salt mixed solution described in step 2 is 0.01-1 mmol / mL.

8. The method for preparing a noble metal-doped NiV layered double hydroxide catalyst according to claim 2 or 3, characterized in that: The drying described in step 3 is natural drying or vacuum drying at a temperature of 50 to 80° C. for 1 to 5 hours.

9. The use of the noble metal-doped NiV layered double hydroxide catalyst according to claim 1, characterized in that: The application is to use precious metal-doped NiV layered double hydroxide catalysts to produce hydrogen in seawater electrolysis.